Politics of Secularism in Ethiopia: Repression or Co-option towards the Ethiopian Orthodox Tewahido Church? - Liyew, Dereje Melese (European Scientific Journal, ESJ, 2024)
Secularism in Ethiopia has not been practiced as stipulated in the 1995 Constitution of the Federal Democratic Republic of Ethiopia (FDRE): separation of state and religion. Instead, consecutive regimes, since the introduction of secularism, have employed a tactic of co-option and repression towards the Ethiopian Orthodox Tewahido Church (EOTC) to meet their political objectives. This research article addresses the nature and manifestation of government intervention in the EOTC through either co-option and/or repression, with a special emphasis on the post-2018 regime. The study argues de-facto secularism in Ethiopia is far from the essence of separation of state and religion; it is a new version of religion industriously implemented by governments to upgrade the Orthodox Church in a way that fits with the political system. The secular regimes co-opted and repressed the church conditionally at any cost to the institution through a Machiavellian approach. The study also finds that the prosperity-led regime was actively involved in the internal affairs of the church in the early days through co-option in the name of reconciliation with the exile synod. In the later days, via repression, massive killings of orthodox followers, burning of churches, and restrictions on the church’s annual ceremony, as in the case of Epiphany and Meskel (Demera), the regime oppressed the church.